Is the organizational culture of the U.S. Army congruent with the professional development of its senior level officer corps? - Pierce, James G. (Strategic Studies Institute, U.S. Army War College, 2010)
"In the present study, Dr. Pierce postulates that the ability of a professional organization to develop future leaders in a manner that perpetuates readiness to cope with future environmental and internal uncertainty depends on organizational culture. Specifically, the purpose of his study is to explore the relationship between the Army's organizational culture and professional development. He examines the degree of congruence between the Army's organizational culture and the leadership and managerial skills of its officer corps senior leaders. He uses data from a representative sample of such leaders while they were students at the Army War College, Classes of 2003 and 2004. At the macro level, the results of his research strongly suggest a significant lack of congruence between the U.S. Army's organizational culture and the results of its professional development programs for its future strategic leaders.
"September 2010."
Includes bibliographical references (p. 117-136)
Summary -- Introduction -- Organizational culture -- Importance of organizational culture analysis -- An overview of professional organizations --Purpose of the present study -- Brief discussion of the concepts of organizational culture and professionalism -- Organizational culture -- Professionalism and professional development -- Methodology -- An overview of the Competing Values Framework (CVF) model -- Origins of the Organizational Culture Assessment Instrument (OCAI) -- An overview of the Management Skills Assessment Instrument (MSAI) -- Methodology of the study -- Findings and analysis -- Organizational Culture Assessment Instrument (OCAI) : findings and analysis -- Final analysis -- Implications -- Overview -- Implications for the army profession
Keywords: United States / Army / Reorganization; United States / Army / Officers / Vocational guidance; United States / Army / Personnel management; Corporate culture / United States; Organizational behavior / United States; Career development / United States; Employee retention; Leader development; Military culture; Reorganisation; Armee; USA